THE ROLE OF STRATEGIC AUDITING IN REDUCING TAX EVASION PROCEDURES: A FIELD STUDY IN THE GENERAL TAX AUTHORITY - Lecturer Alaa Yahya Younis Saeed (Scholar Express Journals, 2025)
The aim of this research is to demonstrate the importance of strategic auditing within the General Tax Authority and its role in reducing tax evasion, as it is one of the tools used to increase the assurance provided by the administration on how to direct taxpayers to pay the tax amount and reduce the number of Tax evaders, and the most important conclusions were (the antiquity of tax legislation with the many amendments to it prevents obtaining effective and influential strategic planning to reduce tax evasion), and the most important recommendations are (the necessity of issuing tax legislation that suits the requirements of the economy and all changes that occur, provided that they are issued within the framework of the strategic plan of the General Tax Authority to reduce tax evasion).
Keywords: Strategic Auditing; Tax Evasion Procedures